Student’s Readiness Level towards Implementation of paper 3 Subject History - Siti Aishah Suhaimi; Mohd Mahzan Awang; Anuar Ahmad (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
This study focuses on the student towards paper implementation 3 subject of history. This study use where survey research design as many as 50 from respondent 4 in School orchid, Cheras, chosen by gregarious sample and use instrument in obtaining quantitative data. This research using Social learning theory Albert Bandura, theory of constructivism and also Bloom's Taxonomy model. Data analyzed by using Excel Microsoft software 2010 (Statistic pack) 2.0 (SPSS). Finding of correlation analysis show there is a significant relationship between student attitude approach with students’ knowledge towards paper of 3 history subject (r, =.846=, n=50, p<.0.5). Therefore, the paper 3 subject of history is seen as platform that is able to increase the understanding and performance of students in the general history often associated with subjects that are boring and hard to get better performance by students in examinations due to lack of interest, learning techniques are obsolete and inadequate learning